Integration of molecular docking and molecular dynamics simulations for studying potential tyrosinase inhibitors from sargassum genus - Dang, Thi Minh Tuyet; Nguyen, Thanh Vinh; Tran, Duy Phong; Pham, Minh Quan; Nguyen, Hai Dang; Nguyen, Thi Nguyet Hang; Bui, Nguyen Thanh Long; Truong, Ngoc Hung; Long, Pham Quoc (Vietnam Journal of Science and Technology, 2025)
The copper-dependent enzyme tyrosinase is vital for the creation of melanin, the pigment responsible for coloration in skin, hair, and eyes. Because of tyrosinase's contribution to unwanted skin darkening, the identification of secure and potent natural inhibitors is a major goal for scientists in the cosmetic and pharmaceutical industries. In this work, a dataset of 71 compounds originated from Sargassum genus has been investigated the ligand-binding affinity to tyrosinase via atomistic simulations. The compounds including difucodiphlorethol A and pseudotrifuhalol A were suggested that can inhibit GSK-3β via molecular docking and molecular dynamic simulations. The residues including His61, His259, Asn260, His263, Arg268, Met280, Gly281, Ser282 and Val283 play a crucial role in the ligand-binding process Furthermore, the toxicity prediction also indicates that these compounds would adopt less toxicity.